New Mediterranean Marine biodiversity records (December, 2013) - M. BILECENOGLU; J.E.F. ALFAYA; E. AZZURRO; R. BALDACCONI; Y.Ö. BOYACI; V. CIRCOSTA; L.J.V. COMPAGNO; F. COPPOLA; A. DEIDUN; H. DURGHAM; F. DURUCAN; D. ERGÜDEN; et al. (Mediterranean Marine Science, 2013)
Based on recent biodiversity studies carried out in different parts of the Mediterranean, the following 19 species are included as new records on the floral or faunal lists of the relevant ecosystems: the green algae Penicillus capitatus (Maltese waters); the nemertean Amphiporus allucens (Iberian Peninsula, Spain); the salp Salpa maxima (Syria); the opistobranchs Felimida britoi and Berghia coerulescens (Aegean Sea, Greece); the dusky shark Carcharhinus obscurus (central-west Mediterranean and Ionian Sea, Italy); Randall’s threadfin bream Nemipterus randalli, the broadbanded cardinalfish Apogon fasciatus and the goby Gobius kolombatovici (Aegean Sea, Turkey); the reticulated leatherjack Stephanolepis diaspros and the halacarid Agaue chevreuxi (Sea of Marmara, Turkey); the slimy liagora Ganonema farinosum, the yellowstripe barracuda Sphyraena chrysotaenia, the rayed pearl oyster Pinctada imbricata radiata and the Persian conch Conomurex persicus (south-eastern Crete, Greece); the blenny Microlipophrys dalmatinus and the bastard grunt Pomadasys incisus (Ionian Sea, Italy); the brown shrimp Farfantepenaeus aztecus (north-eastern Levant, Turkey); the blue-crab Callinectes sapidus (Corfu, Ionian Sea, Greece). In addition, the findings of the following rare species improve currently available biogeographical knowledge: the oceanic pufferfish Lagocephalus lagocephalus (Malta); the yellow sea chub Kyphosus incisor (Almuñécar coast of Spain); the basking shark Cetorhinus maximus and the shortfin mako Isurus oxyrinchus (north-eastern Levant, Turkey).